Synthesis, spectroscopic and X-ray crystallographic properties of manganese compounds of keto- and enol-coordinated di-2-pyridyl ketone benzoyl hydrazone (dpkbh). Reactions of [Mn(CO)5Br] with dpkbh. Issue 7 (2nd April 2016) - Bakir, Mohammed; Conry, Rebecca
Abstract: Reactions between [Mn(CO)5 Br] and dpkbh in low boiling solvents in air gave fac -[Mn I (CO)3 (κ 2 -Npy, Nim -dpkbh)Br]·H2 O, [Mn II Br2 (κ 3 -Npy, Nim, O-dpkbh)], and [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·0.5H2 O (Nim  = imine nitrogen and Npy  = pyridyl nitrogen). Crystallization of fac -[Mn I (CO)3 (κ 2 -Npy, Nim -dpkbh)Br]·H2 O from dmso or CH3 CN produced dark red crystals of [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·nX (X = dmso, n = 1 and X = H2 O, n = 0.22). This is in contrast to the reaction of [Re(CO)5 Cl] with dpkbh in refluxing toluene to form fac -[Re I (CO)3 (κ 2 -, Npy, Npy -dpkbh)Cl] which can be crystallized from CH3 CN, dmso or dmf to form fac -[Re I (CO)3 (κ 2 -, Npy, Npy -dpkbh)Cl]·nX (X = CH3 CN, n = 0 and solvate = dmso or dmf, n = 1). Infrared spectral measurements are consistent with keto coordination of dpkbh to Mn(I) in fac -[Mn I (CO)3 (κ 2 -Npy, Nim -dpkbh)Br]·H2 O and Mn(II) in [Mn II Br2 (κ 3 -Npy, Nim, O-dpkbh)] plus enol coordination of the amide-deprotonated dpkbh, to the Mn(II) center in [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·0.5H2 O. Electronic absorption spectral measurements in non-aqueous solvents indicate sensitivity of fac -[Mn I (CO)3 (κ 2 -Npy, Nim -dpkbh)Br]·H2 O and [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·0.5H2 O to changes in their outer-shell environments. X-ray crystallographic analyses elucidated the identities of [Mn II Br2 (κ 3 -Npy, Nim, O-dpkbh)] and [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·nX and divulged weaker coordination of [dpkbh] to Mn(II) in [Mn II Br2 (κ 3 -Npy, Nim, O-dpkbh)] and stronger coordination of [dpkbh-H] − to Mn(II) in [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]·0.22H2 O. Low-temperature X-ray structural analyses were employed to account for the disorder in the structure of [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ] and the short NH bond distance observed in the structure of [Mn II Br2 (κ 3 -Npy, Nim, O-dpkbh)]. A PLATON Squeeze treatment was invoked to account for the fractional occupancy of lattice water in the structure of [Mn II (κ 3 -Npy, Nim, O-dpkbh-H)2 ]. Abstract :